(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
Proper closed loop has been an ever hot issue in the automotive industry. The industrial equipments governed by PID controllers have very simple control architecture and efficiency but still they find a trouble dueto large power consumption and slow mathematical computation. Many researchers have worked out and are trying to design a low power, less delay PID. This paper reviews three MAC architectures with array, booth and wallace tree multipliers incorporated in PID architecture. The simulations are done and the area, power, delay results are synthesized using Xilinx ISE. Comparisons are made between these three architectures in terms of power delay product and area delay product.